Examining correlates of organizational citizenship behavior and counterproductive work behavior in a collectivist culture: The case of Arab teachers in Israel - Aaron Cohen; Mohammad Abedallah (Organization Management Journal (OMJ), 2021)
Purpose: This study aims to examine the relationships between personal (emotional intelligence, Dark Triad (DT), core self-evaluation and burnout) and situational variables (organizational justice) and organizational citizenship behavior (OCB) (supervisor report) and counterproductive work behavior (CWB) (self-report). Design/methodology/approach: In total, 680 questionnaires were distributed to teachers in 20 Arab elementary schools in Northern Israel. Usable questionnaires were returned by 509 teachers (75%). The questionnaires covered emotional intelligence, DT, core self-evaluation, organizational justice, burnout, CWB and demographic characteristics. Their principals filled out questionnaires on the teachers' in-role performance and OCB. Findings: Results showed that CWB was mostly related to higher levels of psychopathy, lower levels of emotional intelligence (ability to use emotions) and higher levels of burnout (emotional exhaustion). OCB was related to higher levels of procedural justice, lower levels of burnout and higher levels of emotional intelligence. Practical implications: Organizations should consider ways to reduce burnout, which may reduce CWB and increase perceptions of justice, thereby promoting OCB. Originality/value: Two novel aspects are noteworthy. First, this study simultaneously examines both CWB and OCB to clarify the similarities and differences between them. Second, few studies have examined the correlates of CWB and OCB in Arab culture.
Keywords: 650; Burnout; Emotional intelligence; Organizational citizenship behavior; Dark triad; Counterproductive workplace behavior